Loss of Function of an RNA Polymerase III Subunit Leads to Impaired Maize Kernel Development. Issue 1 (26th June 2020) - Zhao, Hailiang; Qin, Yao; Xiao, Ziyi; Li, Qi; Yang, Ning; Pan, Zhenyuan; Gong, Dianming; Sun, Qin; Yang, Fang; Zhang, Zuxin; Wu, Yongrui; Xu, Cao; et al.
Abstract: ZmNRPC2 affects RNAPIII activity and regulates the expression of genes involved in cell proliferation and endoreduplication to control maize kernel development. Abstract: Kernel size is an important factor determining grain yield. Although a number of genes affecting kernel development in maize ( Zea mays ) have been identified by analyzing kernel mutants, most of the corresponding mutants cannot be used in maize breeding programs due to low germination or incomplete seed development. Here, we characterized small kernel7, a recessive small-kernel mutant with a mutation in the gene encoding the second-largest subunit of RNA polymerase III (RNAPΙΙΙ; NRPC2 ). A frame shift in ZmNRPC2 leads to a premature stop codon, resulting in significantly reduced levels of transfer RNAs and 5S ribosomal RNA, which are transcribed by RNAPΙΙΙ. Loss-of-function nrpc2 mutants created by CRISPR/CAS9 showed significantly reduced kernel size due to altered endosperm cell size and number. ZmNRPC2 affects RNAPIII activity and the expression of genes involved in cell proliferation and endoreduplication to control kernel development via physically interacting with RNAPIII subunits RPC53 and AC40, transcription factor class C1 and Floury3. Notably, unlike the semidominant negative mutant floury3, which has defects in starchy endosperm, small kernel7 only affects kernel size but not the composition of kernel storage proteins. Our findings provide novel insights into the molecular network underlying maize kernel size, which could facilitate the genetic improvement of maize in the future.